Customer Satisfaction at Eseva Centres - Appa Rao, V.; Vijaya Shanthi, K. (Indian Journal of Marketing, 2007)
eSeva (Electronic Seva) is an illustration of a hand pump solution in information technology. It is envisaged as an integrated electronic interface where citizens can access government services, pay bills and taxes and obtain necessary information from government regarding schemes and projects. eSeva centre comprising multiple counters through which services would be delivered in a pleasant setting with trained and motivated staff.The eSeva center is a one stop shop for more than 30 Government-to-Consumer (G2C) and Business-to-Consumer (B2C) services including payment of utility bills, reservation of train tickets, getting birth and death certificates, vehicle permits, driving licenses, transport department services, etc. Before the launch of the eSeva project, these services were available at separate offices and were normally time-consuming because of slow processing and often-large crowds waiting for the services. eSeva project has been able to attract the attention of customers and organizations. Various public and private organizations are providing their services through eSeva centers. eSeva has shown phenomenal growth rate in terms of number of transactions and services.